Effect of brush length of stabilizing grafted matrix on size and catalytic activity of metal nanoparticles. (5th July 2020) - Barsbay, Murat; Çaylan Özgür, Tansu; Sütekin, S. Duygu; Güven, Olgun
Graphical abstract: Highlights: PVP-grafted silica with different brush lengths was synthesized via RAFT polymerization. Pd nanoparticles (NPs) of varying sizes were formed in the PVP stabilizing matrix by gamma irradiation. PVP shell was found to be able to control the size of Pd NPs. Longer PVP grafts provided smaller NPs and more stable catalytic activity in repeated reaction cycles. Abstract: The rationale of this work is to investigate the effect of chain length of stabilizing polymer brushes attached to silica surface on the formation and catalytic activity of metallic palladium nanoparticles (Pd NPs). Poly(vinyl pyrrolidone) (PVP) brushes forming a very thin shell were grafted on silica microparticles (PVP@SiO2 ) via RAFT mediated graft polymerization, thus controlling the molecular weights and structures of PVP grafts. Pd nanoparticles were formed in PVP stabilizing matrix by gamma-induced reduction of polymer-bound Pd(II) ions to yield Pd(0) decorated core-shell particles (PVP-PdNP@SiO2 ). SEC and TGA results indicated the formation of PVP brushes with different molecular weights on silica substrate. DLS and TEM measurements revealed that particle growth was sterically blocked by the increase in PVP brush length, thereby forming a greater number of small Pd nanoparticles rather than larger ones. PVP-PdNP@SiO2 samples with different PVP chain lengths and Pd sizes were evaluated for their catalytic activity and reusability in the reduction of 4-nitrophenol to 4-aminophenol. Although the nanoparticles formed in the presence of longer grafted chains are smaller, their leakage into the solution has been found to be more effectively prevented by these long grafts. Thus, PVP-PdNP@SiO2 samples with longer PVP grafts showed more stable catalytic activity in repeated reaction cycles. These findings are particularly important for heterogeneous catalysis systems in that they show the effect of the size of surface-bound polymeric stabilizers on metal NP formation and catalytic activity.